LM02 trial Perioperative treatment with panitumumab and FOLFIRI in patients with wild-type RAS, potentially resectable colorectal cancer liver metastases—a phase II study - Piringer, Gudrun; Gruenberger, Thomas; Thaler, Josef; Kührer, Irene; Kaczirek, Klaus; Längle, Friedrich; Viragos-Toth, Istvan; Amann, Arno; Eisterer, Wolfgang; Függer, Reinhold; Andel, Johannes; Pichler, Angelika; et al. (Frontiers in Oncology, 2023)
20% of colorectal cancer liver metastases (CLM) are initially resectable with a five-year survival rate of 25-40%. Perioperative FOLFOX increases progression free survival (PFS). In advanced disease, the addition of targeting therapies results in an overall survival (OS) advantage. The aim of this study was to evaluate panitumumab and FOLFIRI as perioperative therapy in resectable CLM.Patients with previously untreated, wild-type RAS, resectable CLM were included.Preoperative 4 and postoperative 8 cycles of Panitumumab and FOLFIRI were administered. Primary objectives were efficacy and safety. Secondary endpoints included PFS and OS.We enrolled 36 patients in 7 centers in Austria (ITT-analyses 35 patients). There were 28 men and 7 women, the median age was 66 years. 91.4% completed preoperative therapy and 82.9% underwent liver resection. R0 resection rate was 82.7%. 20 patients started and 12 patients completed postoperative chemotherapy. Objective radiological response rate after preoperative therapy was 65.7%. 20% and 5.7% of patients had stable disease and progressive disease. The most common grade 3 adverse events were diarrhea, rash and leukopenia during preoperative therapy. One patient died due to sepsis and one had a pulmonary embolism grade 4. After surgery, two patients died due to hepatic failure. Most common grade 3 adverse events during postoperative therapy were skin toxicities/rash, leukopenia/neutropenia and two grade 4 adverse events (stroke, intestinal obstruction). Median PFS was 13.2 months. OS rate at 12 and 24 months were 85.6% and 73.3%.Panitumumab and FOLFIRI as perioperative therapy for resectable CLM results in a radiological ORR in 65.7% of patients with a manageable grade 3 diarrhea rate of 14.3%. Median PFS was 13.2 months and 24-month OS rate was 73.3%. These data are insufficient to widen the indication of panitumumab from the unresectable setting to the setting of resectable CLM.